Calor imposto líquido: um novo conceito para quantificação do aporte térmico em soldagem a arco - Liskevych, Olga (2014)
A more detailed and accurate study of the thermal phenomena involved in arc welding processes is of great importance for both simulation developers of metallurgical transformations and residual stresses generation and users in general, whom need to understand this phenomenology to take decisions. In terms of thermal phenomena, heat input and its derivatives (such as thermal efficiency and fusion efficiency are the most representative parameters in welding engineering. However, scientific and technical literatures are very divergent on heat input values. In addition, they do not discuss the actual heat flow inside the plate. Initial tests demonstrated that these inconsistencies are due to systematic and random errors that occur during heat input measurements. Thus, the major purpose of this work was to develop a methodological approach to determine the heat input due to a welding process, which would be more representative of the heat that actually diffuses inside the workpiece and free of the assessment method and parameter influence. Thus, this actual heat input could be generally used in calculations that require this welding parameter. As methodological base, a descriptive model of heat flow in the welding region was developed. Then, a methodology to determine a heat input value free of measurement errors (here called as net heat input) was proposed and applied to cryogenic calorimetry. This procedure was validated using several welding conditions. The results demonstrated the proper functioning of the proposed methodology, regardless the welding process and its variables. It is expected that, with the application of the net heat input values, the calculations and simulations involved in welding engineering turn into more robust, since the use of such imprecise parameter as thermal efficiency is dispensed.